PENGARUH MEKANISME CORPORATE GOVERNANCE DAN PROFITABILITAS TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2015) - Yuni Mayasari Girsang; Desmiyawati Desmiyawati; Mudrika Mudrika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study uses secondary data (secondary data), ie data from audited financial statements and audited annual reports. This study aims to determine the effect of corporate governance and profitability mechanisms on the timeliness of financial reporting. The population in this study are all companies listed on the Indonesia Stock Exchange in 2013 as many as 486 companies. Sampling in this research using purposive sampling method, that is sample selected from population with predefined criteria. Data analysis method used in this research is logistic regression model.The results of this study show the effect on the timeliness of financial reporting. Independent Commissioner affects the timeliness of corporate financial reporting. Managerial ownership does not affect the timeliness of corporate financial reporting. Institutional ownership affects the timeliness of corporate financial reporting. The audit committee has no effect on the timeliness of corporate financial reporting. Audit quality affects the timeliness of corporate financial reporting. Profitability affects the timeliness of corporate financial reporting. The result of determination coefficient test (R2) is 0,536 and it can be illustrated that 53,6% variable of timeliness of financial reporting can be explained by variable consisting of corporate governance and profitability mechanism, while 46,4% is explained by other variable.Keywords : Corporate Governance Mechanism, Profitability and Timeliness of Financial Reportin